Influence of Municipal Abattoir Conditions and Animal-related Factors on Avoidance-related Behaviour, Bleeding Times at Slaughter and the Quality of Lamb Meat - Njisane, Yonela Z. (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2013)
The objective of this study was to determine the effect of municipal abattoir conditions and animal factors on avoidance-related behaviour (AB) of sheep at slaughter, bleeding times (BT) and mutton quality. The behaviour of 66 castrates and 19 ewes of different age categories was observed at three stages of slaughter. Higher behaviour scores indicated higher levels of AB. Time intervals between the start of blood flow and the time the flow changed from a constant stream into drips were recorded as BT. Thirty two meat samples were obtained to measure quality variables. These were colour (L*, a* and b*), pH(24), temperature, cooking loss (CL) and tenderness. Correlations were determined between BT and meat quality variables. Animal behaviour at slaughter differed with breed, gender and age group. Avoidance behaviour was higher in the Dorper breed than in both the Merino breed and their crosses. It was also higher in younger (<10 months) lambs than in older sheep. Castrates were more aggressive or in panic than ewes. Castrates had longer (72.6±0.53 s) BT than the ewes (63.6±2.82 s). Ewes had higher CL (39.8±1.04%) values than castrates (35.1±0.95%). Meat from castrates was tougher (32.6±1.95 N) than the meat from ewes (24.3±1.16 N). There were no significant correlations obtained between BT and meat quality variables. It can therefore be concluded that abattoir conditions, breed, age and gender had an effect on AB at slaughter. Gender had an effect on BT and mutton quality.